Two-step ion-exchanged soda lime silicate glass: Effect of surface compression on silver ion release - Talimian, Ali; Nowicka, Aleksandra; Kankova, Hana; Sani, Gohar; Galuskova, Dagmar; Wondraczek, Lothar; Galusek, Dusan (International Journal of Applied Glass Science, 2021)
Although glass plays an important role in medical facilities such as countertops or interfaces of medical equipment, where chemical and mechanical durability is of great concern, less attention has been paid to developing durable anti-microbial surfaces. In the present work, silver-containing surfaces were produced by ion exchange in soda-lime silicate float glass, and the effects of residual surface compression produced by ion-exchange on the release of silver ions were investigated. Silver-doped surfaces were prepared by a sequential two-stage ion-exchange process in pure potassium nitrate, at 450°C for 4-24 hours, and subsequently in KNO3+ 1 wt% AgNO3, at 400°C for 10-30 minutes. Silver ions were found to penetrate 3-5 µm into the glass surface, causing only a limited decrease in surface compression induced by potassium ions. The silver-rich layer provides the required Ag+ leaching essential for anti-microbial applications, as confirmed by Ag+ ion leaching tests. The silver release can be altered by surface compression.
CRIS-Team Scopus Importer:2023-04-20
Keywords: ion release; ion-exchange; soda-lime silicate; strengthening